PENGGUNAAN RETORIKA DALAM PIDATO PENGUNDURAN DIRI MIKHAIL GORBACHEV: KAJIAN WACANA KRITIS NORMAN FAIRCLOUGH - Raynadi, Muhammad Shanneva (UI Scholars Hub, 2025)
This study analyzes the use of rhetoric in Mikhail Gorbachev's resignation speech on December 25, 1991, using one of Norman Fairclough's Critical Discourse Analysis (CDA) approach, namely rhetorical aspect. This speech marked the dissolution of the Soviet Union and reflected the socio-political changes during Gorbachev's leadership, particularly concerning glasnost (openness) and perestroika (restructuring) policies. Through an analysis of Aristotle's five rhetorical elements—inventio, dispositio, elocutio, memoria, and pronuntiatio—this study finds that Gorbachev employed rhetorical strategies to reframe his reform ideas, establish credibility, and influence public perception of the ongoing political transition. The findings indicate that the speech was not merely a formal declaration but also a political communication tool aimed at reinforcing the legitimacy of his reforms and shaping public opinion.